PENGARUH KOMITE AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN WHISTLEBLOWING SYSTEM SEBAGAI VARIABEL MODERASI - Irma Paramita Sofia (Jurnal Riset Akuntansi Terpadu, 2018)
This study aims to examine the effect of audit commitee on Financial Statement’s integrity. In addition, this study wanted to test whistleblowing policy as a moderating variable on the relationship between audit committee on Financial Statement’s integrity. Independent variables used in this research are audit commitee. Dependent variable used in this research is Financial Statement’s integrity. While the moderation variable used in this research is whistleblowing policy. The sample in this research is banking company with the largest total assets listed on Indonesia Stock Exchange in the period 2014-2016. Analysis of data using multiple linear regression, and to determine the hypothesis used t-test and F-test. The results of this study indicate that audit commitee positively affect Financial Statement’s integrity. Whistleblowing policy is able to moderate the relationship between audit commitee on Financial Statement’s integrity.